Chronic Renal Changes After a Single Ischemic Event in an Experimental Model of Feline Chronic Kidney Disease. Issue 4 (July 2019) - Brown, Cathy A.; Rissi, Daniel R.; Dickerson, Vanna M.; Davis, Anastacia M.; Brown, Scott A.; Schmiedt, Chad W.
Previous work demonstrated renal fibrosis 70 days after a single unilateral in vivo renal ischemic event, but changes associated with a single episode of renal ischemia past this time are unknown. In this study, we evaluated renal function and structural changes 6 months after a 90-minute in vivo unilateral renal ischemic event. Six adult female cats underwent unilateral renal ischemia and renal function was followed for 6 months, at which time the kidneys were evaluated by histology and histomorphometry. Over time, there was a significant reduction in the glomerular filtration rate and an elevation of serum creatinine of 31% and 42%, respectively. All cats had tubulointerstitial lesions characterized by segmental interstitial inflammation, tubular atrophy, and interstitial fibrosis. Unlike short-term studies, ischemic kidneys had variable numbers of obsolescent glomeruli, consistent with the development of atubular glomeruli and subsequent ischemic glomerulosclerosis. Chronic changes associated with acute renal ischemia may include loss of function and glomerulosclerosis.